Influence of concentrate-rice straw ammoniated ratio and fattening period on body weight and meat physical quality of Pesisir cattle - ., Khasrad; ., Rusdimansyah (Indonesian Journal of Animal and Veterinary Sciences, 2012)
Pesisir cattle, an original local cattle of West Sumatera, have good genetic potential because they adapt very well to both the low-quality feed, and changes in ambient temperature. This research was conducted to determine body weight, feed consumption and conversion, daily gain and meat quality (tenderness, water holding capacity, cooking loss and pH) of Pesisir cattle in different ration composition and feedlot period. This experiment was done based on Randomized Block Design in 2 x 2 factors with 3 groups. The first factor (factor A) was two kinds of diet i.e. A1 = 50% concentrate + 50% ammoniated rice straw and A2 = 75% concentrate + 25% ammoniated rice straw. The second factor (factor B) was duration of fattening (B1) i.e. 3 months and (B2) 4 months. There was no interaction between the level of the diet with duration of fattening on body weight, daily gain, tenderness, water holding capacity and cooking loss on meat of Pesisir cattle (P> 0.05). Body weight in A2 group was significantly higher than A1 beginning from second month of treatment. Factor A had significant effect on daily gain. The pH value of meat of cattle that received 75% concentrate was lower than that received 50% concentrate. The higher the percentage of concentrate in diet caused better body weight, daily gain, consumption, feed conversion and tenderness. Duration of fattening did not resulted in significant effect on all of parameters except final weight. Key Words: Pesisir Cattle, Feedlot, Ammoniated Rice Straw, Physical Meat Quality